Analisis Penataan Sistem Drainase Sebagai Pengembangan Edu-Tourism Khaira Ummah di Kampus Unissula Semarang - Ashari, Mochamad Hisam; Mudiyono, Rachmat; Soedarsono, Soedarsono (Pondasi, 2023)
Floods and Rob floods are natural disasters that often occur in Indonesia. The UNISSULA campus area is in the Pantura road area. UNISSULA is one of the campuses affected by floods and robs. Extreme weather conditions and rising sea levels have exacerbated the condition of the north coast road. Thus causing traffic jams and activities of the surrounding community to falter.The purpose of this study was to analyze the drainage system of the UNISSULA campus area by utilizing the potential of a storage pond by disposing of water directly into the estuary. With this research, it is hoped that it can be used as data and material for consideration for the development of a drainage system in the campus area and to become a pilot campus to control flooding. The method used is a simulation of the rainfall-runoff model using EPA SWMM Version 5.1.This study carried out two scenarios in carrying out flood control efforts, namely the first scenario, the existing west, and east retention ponds will be connected to pond 1, for the pond in the north, will be connected from pool 4 to the engineering pool, channeled to pool 3, to pool 2 and connected with pool 1 equipped with a pump with a capacity of 1 m3/sec with additional long storage from pool 2 to pool 1 along 184 meters. The second scenario is to break the direction of the front and rear drainage flows. For drainage, it will be pulled into pond 4, then a technical pond until it is connected to pool 2 and discharged directly into the sea with a flood pump with a capacity of 0.5 m3/sec. This makes the flood travel time short and is expected to reduce inundation. With this scenario, it can also be developed as Khairu UmmahÂ Edu-tourism Khaira UmmahÂ in the campus area.